Ugly differences : queer female sexuality in the underground - Howard, Yetta (University of Illinois Press, 2018)
'Ugly Differences' explores queer female sexuality's symbiotic relationship with ugliness and offers a way to see worth in ugliness as a generative category for reimagining the inhabitation of gender, sexual, and ethnic differences. Ugliness, in this work, is a multipronged concept: it equates with the disagreeable and pejorative traits that are attributed to queerness; it aligns itself with nonwhite, nonmale, and nonheterosexual physicality and experience; and it refers to anti-aesthetic textual practices, which are located in/as underground culture.